Validation of the Indonesian Version of the Multidimensional Scale of Perceived Social Support (MSPSS): A Rasch Model Approach - Wiwik Sulistiani; Fajrianthi Fajrianthi; Ika Febrian Kristiana (Jurnal Psikologi, 2022)
Scale adaptation in different cultures is needed to ensure that the scale measures the intended target. The Multidimensional Scale of Perceived Social Support (MSPSS) has been adopted in several countries, but no Indonesian language adaptation has been made so far. This study aims to test the construct validity of the Indonesian MSPSS that measures one’s level of social support. Rasch analysis was used to examine the psychometric properties of the scale. The subject in this study was 495 Indonesian marine cadets with an average age of 19.32 (41% Engineering, 52.7% Nautical, and 5.5% Electro). In terms of gender, 94.3% were male and 5.7% female. Findings from the Rasch analysis support the one-dimensionality of the 12-items MSPSS in measuring marine cadets’ level of social support. This finding differs from similar MSPSS studies that show the scale’s structure to be multidimensional. The 12-items MSPSS showed excellent internal consistency (person-item interaction index = .85) and fulfilled all the Rasch model requirements. No item misfit was detected from the MNSQ score (.5 < MNSQ < 1.5). Also, there was no item bias based on gender was detected from the scale (.0949 - .9687) > .05. Future studies are advised to test the scale with different samples to further confirm this study’s findings.